2021
DOI: 10.1002/mus.27216
|View full text |Cite
|
Sign up to set email alerts
|

hnRNP L is essential for myogenic differentiation and modulates myotonic dystrophy pathologies

Abstract: Introduction: RNA-binding proteins (RBPs) play an important role in skeletal muscle development and disease by regulating RNA splicing. In myotonic dystrophy type 1 (DM1), the RBP MBNL1 (muscleblind-like) is sequestered by toxic CUG repeats, leading to missplicing of MBNL1 targets. Mounting evidence from the literature has implicated other factors in the pathogenesis of DM1. Herein we sought to evaluate the functional role of the splicing factor hnRNP L in normal and DM1 muscle cells.Methods: Co-immunoprecipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…DDX5 may directly interact with hnRNP F/H and facilitate its binding to highly structured G-quadruplex-enriched regions, thus initiating myoblast-specific splicing programs and regulating myogenic differentiation ( Dardenne et al, 2014 ). In DM1 muscles, hnRNP L may regulate the same targets as MBNL1, which is consistent with the their physical interaction ( Alexander et al, 2021 ). It is also of note that RBM24 interacts with several RBPs of the cytoplasmic polyadenylation complex, including PABPC1 and CPEB4, to regulate poly(A) tail length ( Shao et al, 2020 ).…”
Section: Functional Interactions Between Rna-binding Proteins Coordinate Gene Expression During Myogenesissupporting
confidence: 70%
See 2 more Smart Citations
“…DDX5 may directly interact with hnRNP F/H and facilitate its binding to highly structured G-quadruplex-enriched regions, thus initiating myoblast-specific splicing programs and regulating myogenic differentiation ( Dardenne et al, 2014 ). In DM1 muscles, hnRNP L may regulate the same targets as MBNL1, which is consistent with the their physical interaction ( Alexander et al, 2021 ). It is also of note that RBM24 interacts with several RBPs of the cytoplasmic polyadenylation complex, including PABPC1 and CPEB4, to regulate poly(A) tail length ( Shao et al, 2020 ).…”
Section: Functional Interactions Between Rna-binding Proteins Coordinate Gene Expression During Myogenesissupporting
confidence: 70%
“…Its expression level increases during myogenic differentiation in normal human myoblasts. Knockdown of hnRNP L in zebrafish and human cell lines reduces muscle birefringence and impairs myoblast fusion, respectively ( Alexander et al, 2021 ). Moreover, hnRNP L may be also involved in maintaining muscle homeostasis and in modulating DM1 pathologies because it complexes with MBNL1 and forms nuclear protein aggregates in DM1 myoblasts, which partially colocalize with toxic CUG repeats.…”
Section: Rna-binding Proteins Involved In Skeletal Muscle Development Regeneration and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that MBNL1 is downregulated in DM1 models and patients, and the overexpression of MBNL1 is beneficial in murine disease models [ 5 , 12 ]. Various drugs and epigenetic approaches have been found to promote endogenous MBNL1 expression and ameliorate the disease phenotypes in different experimental models [ 31 34 ]. In the current study, we identified that calcitriol (active form of vitamin D3) elevated MBNL1 expression in mouse myogenic cells and in skeletal muscles of HSA LR mouse model via enhancing the Mbnl1 promoter activity.…”
Section: Discussionmentioning
confidence: 99%
“…The disruption of this careful balance can lead to aberrant gene expression, which in turn can contribute to prominent complex diseases such as cancer [6][7][8][9]. Mutations in RBPs have also been directly linked to a variety of inherited human diseases, which includes orphan diseases [6], such as mutations in fragile X mental retardation protein (FMRP) leading to fragile X-associated tremor/ataxia syndrome (FXTAS) [10], and muscleblind-like 1 (MBNL1) in myotonic dystrophy type 1 [11]. Interestingly, the top Mendelian disorders affected by RBP mutations tend to be diseases of the nervous system, pathologies of the metabolism, and cell proliferation disorders including certain cancers [6].…”
Section: Introductionmentioning
confidence: 99%